Clinical outcomes of frozen embryo versus fresh embryo transfer following in vitro fertilization: a meta-analysis of randomized controlled trials - Zhang, Wanlin; Xiao, Xifeng; Zhang, Junyan; Wang, Wenjun; Wu, Jing; Peng, Ling; Wang, Xiaohong (Archives of gynecology and obstetrics, 2018)
Purpose To examine available data from randomized controlled trials to assess if the freeze-all embryo and subsequent frozen-thawed embryo transfer (FET) results in better clinical outcomes than fresh embryo transfer (ET). Methods Meta-analysis. Results We conducted an electronic literature search on PubMed and Embase databases and manually supplemented another 2 articles from relevant citations. Seven studies were finally included in the meta-analysis,including 1141 women who underwent fresh embryo transfer and 1079 who underwent frozen embryo transfer. The results of the meta-analysis suggested that the live birth rate [RR (95% CI) 1.18 (1.08–1.30), P = 0.0003] and clinical pregnancy rate [RR (95% CI) 1.10 (1.02–1.19), P = 0.02] were significantly higher in FET group. Miscarriage rate [RR (95% CI) 0.62 (0.48–0.80), P = 0.0002], and moderate to severe OHSS occurrence rate [RR (95% CI) 0.22 (0.12 to 0.39), P < 0.00001] were significantly lower in FET group. Differences of biochemical pregnancy rate, ongoing pregnancy rate and implantation rate between the two groups did not reach the statistical significance. Conclusions Our results suggest that the IVF/ICSI with FET is more efficient and less risky for OHSS compared with ET. However, we should comprehensively inform patients with advantages, disadvantages and potential risks related to embryo cryopreservation, and carefully assess their fertility conditions to make the most beneficial clinical decision.